The effectiveness of walking as an intervention for low back pain: a systematic review - Hendrick, P. (Springer-Verlag, 2010)
As current low back pain (LBP) guidelines do not specifically advocate walking as an intervention, this review has explored for the effectiveness of walking in managing acute and chronic LBP. CINAHL, Medline, AMED, EMBASE, PubMed, Cochrane and Scopus databases, as well as a hand search of reference lists of retrieved articles, were searched. The search was restricted to studies in the English language. Studies were included when walking was identified as an intervention. Four studies met inclusion criteria, and were assessed with a quality checklist. Three lower ranked studies reported a reduction in LBP from a walking intervention, while the highest ranked study observed no effect. Heterogeneity of study design made it difficult to draw comparisons between studies. There is only low–moderate evidence for walking as an effective intervention strategy for LBP. Further investigation is required to investigate the strength of effect for walking as a primary intervention in the management of acute and chronic LBP.